Promoting Healthcare Sustainability in Developing Countries: Analysis of Knowledge Management Drivers in Public and Private Hospitals of Pakistan - Karamat, Jawad; Shurong, Tong; Ahmad, Naveed; Afridi, Sana; Khan, Shahbaz; Mahmood, Kashif (International journal of environmental research and public health, 2019)
Investing in a sustainable future has no alternative; the healthcare sector in developing countries has failed to achieve sustainability objectives. Knowledge management (KM) is a concrete application of sustainability in healthcare, as organizations (hospitals) that manage their knowledge assets will gain sustainable competitive advantage. Several organizations in developed countries are moving towards the adoption of knowledge management so that they can manage their knowledge well and improve their performance. Due to the effective implementation of KM in developed countries, developing countries are also considering adopting KM in their healthcare. In this study, an attempt has been made to identify the drivers of KM adoption in public and private hospitals of Pakistan. With the help of an extensive literature review and expert opinion, the drivers were identified and a hierarchical structure was developed. Nineteen drivers were identified and screened out by experts. The experts identified the contextual relationships between the drivers during a brainstorming session. The hierarchical model of the drivers for KM in the healthcare of Pakistan was eventually developed using interpretive structural modeling (ISM). The structure has 10 levels, in which “developed competitive advantage” formed the foundation of the structure and “job creation” and “improvement in the reputation of healthcare” formed the topmost level. The “Matrices d’Impacts Croises Multiplication Appliqué a un Classement” (MICMAC) analysis classified the drivers by categorizing them according to their driving and dependence powers. One driver is identified as autonomous, six drivers as dependent, seven drivers as linkage, and five drivers as independent. The analysis of KM drivers will provide a good understanding of the interdependence and interactions between them and support the effect adoption of KM in developing countries especially in Pakistan.